Basic Leadership Theory: An Ethical Leadership Approach to Developing Positive Lecturer Engagement - Adi Rahmat; Hardi Hardi; Nurfaisal Nurfaisal; Ali Asfar; M. Fadhly Farhy Abbas (STAI Hubbulwathan Duri, 2024)
This study introduces the foundational leadership theory (FLT), an alternative ethical theory, to better understand the relationship between ethics and work engagement in higher education. The research was conducted at a private university in Pekanbaru City, focusing on the fields of management and accounting. Using a census sampling technique, 195 lecturers participated as respondents. Data analysis explored the predictive power of FLT's components—wisdom, affirmation, and pragmatism—on lecturers’ work engagement. The findings revealed that wisdom, affirmation, and pragmatism significantly and positively influence work engagement among lecturers. FLT, as a novel theory, provides a fresh perspective on understanding employee enthusiasm and organizational commitment. Human resource management (HRM) practices that emphasize FLT-based leadership can enhance employees’ eagerness and engagement, helping organizations maintain a competitive advantage. The results underscore the relevance of ethical leadership frameworks like FLT in fostering a motivated and engaged workforce. Further exploration of FLT’s role in mediating or moderating other ethical leadership practices may expand its applicability. Additionally, demographic factors such as race and income level warrant investigation to assess their impact on work engagement. FLT offers valuable insights into ethical leadership and its effect on employee engagement in higher education. Future research should consider other alternative ethical leadership styles to deepen our understanding of organizational commitment and work engagement dynamics.